2021
DOI: 10.2217/pmt-2021-0023
|View full text |Cite
|
Sign up to set email alerts
|

KPI-121 1% for Pain and Inflammation in Ocular Surgery

Abstract: Pain and inflammation are common experiences following ocular surgery and, if uncontrolled, can compromise patients’ vision, functioning and quality of life. Corticosteroid drugs are available to manage inflammation and discomfort but have limitations in penetrating the ocular mucus barrier to reach the target ocular tissues. KPI-121 1% (INVELTYS®) is a novel formulation of loteprednol etabonate that employs innovative proprietary technology to deliver nanoparticle-sized mucus-penetrating particles to the corn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…22 KPI-121 is a nano-based drug delivery system using mucuspenetrating particles to deliver a custom-engineered ocular corticosteroid, loteprednol etabonate, to the ocular surface tissues. [23][24][25][26] In the clinical trial of its application in dry eye disease, there was a low incidence of treatment-related adverse events (AEs), severe AEs, and serious AEs. The only AE reported with an incidence of more than 1% was pain at the site of instillation, which was reported by 5.2% of subjects in the KPI-121 group and 4.4% of subjects in the placebo group.…”
Section: Complications In Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 KPI-121 is a nano-based drug delivery system using mucuspenetrating particles to deliver a custom-engineered ocular corticosteroid, loteprednol etabonate, to the ocular surface tissues. [23][24][25][26] In the clinical trial of its application in dry eye disease, there was a low incidence of treatment-related adverse events (AEs), severe AEs, and serious AEs. The only AE reported with an incidence of more than 1% was pain at the site of instillation, which was reported by 5.2% of subjects in the KPI-121 group and 4.4% of subjects in the placebo group.…”
Section: Complications In Clinical Trialsmentioning
confidence: 99%
“…24 But the pain was transient and mild or moderate in severity. 25,26 NOVA22007 is a proprietary cationic emulsion that enables an optimal penetration of CsA through the ocular surface by Novasorb cationic emulsion technology. 27 In a multicenter phase III trial of NOVA22007 for the treatment of vernal keratoconjunctivitis in children, instillation site pain was also the most common adverse event, reported by six patients (10.5%) in the four-times-daily treatment regimen group, three patients (5.6%) in the twice-daily treatment regimen group, and two patients (3.4%) in the placebo group.…”
Section: Complications In Clinical Trialsmentioning
confidence: 99%
“…The literature does not clearly establish an optimal AIM regimen, dosing, or duration of treatment. [1][2][3][4][5][6][7][8] Some ophthalmologists prescribe either corticosteroids or NSAIDs as topical monotherapy; others prescribe both in combination, potentially as a result of the ESCRS randomized clinical trial that showed that patients treated with combination therapy had a reduced likelihood of developing clinically significant cystoid macular edema compared with those receiving topical monotherapy. 9 More recently, alternate routes of corticosteroid administration have been tried and adopted in an effort to reduce the need or frequency of topical AIM.…”
mentioning
confidence: 99%